Pyridine on flat Pt(111) and stepped Pt(355) - An in situ HRXPS investigation of adsorption and thermal evolution - Steinrück, Hans-Peter; Welke, Martin; Eilert, Andre; Denecke, Reinhard; Schoeppke, Matthias; Wöckel, Claudia (Journal of Chemical Physics, 2016)
We investigated the adsorption and reaction of pyridine on flat Pt(111) and stepped Pt(355) surfaces via high-resolution in situ x-ray photoelectron spectroscopy. The surfaces were exposed to pyridine at temperatures between 112 and 300 K while simultaneously recording XP spectra. Subsequently, the crystals were annealed and the temperature dependencies of the N 1s and C 1s core levels were studied again in a continuous and quantitative way. Various surface species were found, namely, physisorbed, flat-lying and end-on pyridine, α-pyridyl species on the terraces and on the steps and several unidentified high temperature species. We were able to show an influence of the steps of Pt(355) by pre-adsorbing silver next to the step, which selectively suppresses the step adsorption.